D-Serine: A Cross Species Review of Safety - Meftah, Amir; Hasegawa, Hiroshi; Kantrowitz, Joshua T. (Frontiers in psychiatry, 2021)
Background: D- Serine, a direct, full agonist at the D- serine/glycine modulatory site of the N-methyl-D-aspartate-type glutamate receptors (NMDAR), has been assessed as a treatment for multiple psychiatric and neurological conditions. Based on studies in rats, concerns of nephrotoxicity have limited D- serine research in humans, particularly using high doses. A review of D- serine's safety is timely and pertinent, as D- serine remains under active study for schizophrenia, both directly (R61 MH116093) and indirectly through D- amino acid oxidase ( D AAO) inhibitors. The principal focus is on nephrotoxicity, but safety in other physiologic and pathophysiologic systems are also reviewed. Methods: Using the search terms “ D- serine,” “ D- serine and schizophrenia,” “ D- serine and safety,” “ D- serine and nephrotoxicity” in PubMed, we conducted a systematic review on D- serine safety. D- serine physiology, dose-response and efficacy in clinical studies and d AAO inhibitor safety is also discussed. Results: When D- serine doses >500 mg/kg are used in rats, nephrotoxicity, manifesting as an acute tubular necrosis syndrome, seen within hours of administration is highly common, if not universal. In other species, however, D -serine induced nephrotoxicity has not been reported, even in other rodent species such as mice and rabbits. Even in rats, D- -serine related toxicity is dose dependent and reversible; and does not appear to be present in rats at doses producing an acute Cmax of <2,000 nmol/mL. For comparison, the Cmax of D- serine 120 mg/kg, the highest dose tested in humans, is ~500 nmol/mL in acute dosing. Across all published human studies, only one subject has been reported to have abnormal renal values related to D- serine treatment. This abnormality did not clearly map on to the acute tubular necrosis syndrome seen in rats, and fully resolved within a few days of stopping treatment. D AAO inhibitors may be nephroprotective. D- Serine may have a physiologic role in metabolic, extra-pyramidal, cardiac and other systems, but no other clinically significant safety concerns are revealed in the literature. Conclusions: Even before considering human to rat differences in renal physiology, using current FDA guided monitoring paradigms, D- serine appears safe at currently studied maximal doses, with potential safety in combination with D AAO inhibitors.